MODEL PENDIDIKAN ANAK DENGAN KECERDASAN ISTIMEWA JENJANG SD BERBASIS INDIVIDUALIZED EDUCATIONAL PROGRAMS - Mohammad Efendi; Rina Rifqie Mariana (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: Model of elementary school age children education with very high intelligence on the basis of individualized educational programs. Purpose of the research was to product service instruments for developing potency of elementary schools’ students with very high intelligence on the basis of individualized programs. Design of the research was research & development with steps: conducting exploration, identification and analysis characteristic of elementary school. Research results concluded elementary schools’ children were not exist in all times and educational service appropriate to children with very high intelligence tended to enrichment direction. It can be recommended that schools apply minimal service model with enrichment, but if institutions have supporting relevant resources they can use other two options, i.e. acceleration and cluster grouping.Keywords: educational model, very high intelligence, IEPAbstrak: Penelitian ini bertujuan menghasilkan perangkat model layanan untuk mengembangkan potensi kecerdasan istimewa siswa Sekolah Dasar (SD) berbasis pada Individualized Programs. Rancangan penelitian pengembangan, tahap kegiatan melakukan eksplorasi identifikasi dan analisis karakteristik SD. Hasil penelitian diperoleh kesimpulan bahwa anak cerdas di SD tidak hadir sepanjang waktu, dan model layanan pendidikan kepada siswa unggul atau cerdas istimewa cenderung ke arah pengayaan (enrichment). Disarankan, sekolah dapat menerapkan model layanan minimal bersifat pengayaan (enrichment), namun jika lembaga memiliki kesiapan sumber daya penunjang yang relevan dapat memanfaatkan dua opsi model yang lain yakni percepatan (acceleration) dan pengelompokan khusus (cluster grouping).Kata Kunci: model pendidikan, cerdas istimewa, IEP